Pola Komunikasi Ketua Jurusan Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga - Riyan Riyan; Erlina Yuliyati (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2021)
As social beings, humans always communicate. The communication made by the head of the department is a strategy in managing the course of the organization so that it runs as expected. Various impacts will arise if in an organization, including education, when there is miscommunication, including errors in decision making, the interruption does not reach the communicant, and there is no feedback. This research method uses qualitative types and data is obtained through interviews. The results of the study were (1) the communication pattern used by the head of the Department of Islamic Education Management at FITK UIN Sunan Kalijaga was a non-formal form. (2) Constraints in communication usually occur misunderstandings from both the communicator and the communicant, because it does not fit the situation and conditions. (3) Establishing communication with MPI throughout Indonesia through an organization called the MPI Study Program Communication Forum (FKPS MPI) and the Islamic Education Management Study Program Association (PPMPI).